2019
DOI: 10.1002/pssb.201800743
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of Cu2MnSnS4 from Experiment and First‐Principles Calculations

Abstract: Cu 2 MnSnS 4 shares several promising properties with the widely investigated Cu 2 ZnSnS 4 for photovoltaic applications such as containing only earth abundant and non-toxic elements, and suitable absorption characteristics for absorber materials. Thin film Cu 2 MnSnS 4 samples with various cation compositions are co-sputtered reactively followed by a high temperature anneal. Formation of Cu 2 MnSnS 4 and co-existence of several secondary phases is verified by XRD and Raman. Our investigation of the crystal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…In terms of solar cell application, CMTS thin film is considered as absorber layer due to its similarly high absorption coefficient (>10 4 cm −1 ) [142]. The direct band-gap of CMTS was calculated to be 1.52 eV which coincides with the measured 1.42-1.59 eV [143]. From reversible annealing treatments it was also concluded that just like CZTS disorder also occurs in CMTS.…”
Section: Group Vii-b and Viii-bsupporting
confidence: 58%
“…In terms of solar cell application, CMTS thin film is considered as absorber layer due to its similarly high absorption coefficient (>10 4 cm −1 ) [142]. The direct band-gap of CMTS was calculated to be 1.52 eV which coincides with the measured 1.42-1.59 eV [143]. From reversible annealing treatments it was also concluded that just like CZTS disorder also occurs in CMTS.…”
Section: Group Vii-b and Viii-bsupporting
confidence: 58%
“…The anti-ferromagnetic P 4 structure is 17 meV less stable than the anti-ferromagnetic ST phase at the PBE level. Our results on the relative KS and ST stability agree closely with PBEsol calculations by Scragg et al [32]. The same group has also carried out HSE06 calculations and found the ST structure to be more stable than the KS structure.…”
Section: Equilibrium Structuressupporting
confidence: 91%
“…Furthermore, this phase-control mechanism can be expanded to other quaternary Cu 2 MSnS 4 (M = Cd 2+ , Mn 2+ ) nanocrystal syntheses, where the relative reactivity of M 2+ and the sulfur precursor plays a key role. Cu 2 MnSnS 4 (CMTS) has several promising properties in common with Cu 2 ZnSnS 4 , which has been extensively studied for photovoltaic applications since it contains only non-toxic Earth-abundant elements and appropriate absorption properties for absorber materials [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be resistant to cation disorder, similar to the stannite Cu 2 FeSnS 4 . Liang et al describe the synthesis of stannite and wurtzite CMTS nanocrystals via a hot injection approach [13].…”
Section: Introductionmentioning
confidence: 99%